Call for a hybrid model of Zakāh disbursement in Sri Lanka - Jiffr, Mohammed Arafath Careem Mohammed; Zaroum, AbdulHamid Mohamed Ali; Rahmani, Ataollah; Mat Jubri@Shamsuddin, Mustafa (2023)
This paper chiefly is focused on analyzing the disbursement system of Sri Lankan voluntary zakāh institutions. Although the institutionalization of zakāh has been in existence for several decades, its impact on the socio-economic condition of the Sri Lankan Muslim minority remains limited. According to some preliminary studies, the dominant consumption-oriented zakāh disbursement is a prime factor hampering the materialization of multiple socio-economic objectives of zakāh in the Sri Lankan pluralistic context. This study deployed the qualitative method along with content analysis to analyze the relevant data collected from the interviews and the existing literature on the subject. This study proposes that the current consumption-oriented distribution should be combined with the result-oriented distribution and carried out at all regional levels in a standard and well-planned manner that is capable to accommodate the investment and skill-oriented distributing systems. Such a hybrid mode of disbursement would contribute to realizing the broader objectives of zakāh for Muslim minorities in Sri Lanka.